2020
DOI: 10.1002/ajpa.24077
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐isotope, multi‐tissue study of colonial origins and diet in New Zealand

Abstract: Objectives: Colonial period New Zealand was lauded as a land of plenty, where colonists could improve their station in life and secure a future for their families. Our understanding of colonial experience, however, is often shaped by historical records which communicate a state-sponsored version of history. This study aims to reconstruct the lives of settlers using isotopic evidence from the colonial skeletons themselves. Materials and Methods:We use skeletal remains from recently excavated colonial sites in O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 64 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…Enamel carbonate (δ 13 C apatite ) values plotted against dentinal collagen (δ 13 C collagen ) values. MS1‐4 (red circles) are individuals from the Dee St assemblage and MS6 is the modern individual (yellow circle), dietary lines generated using data from King et al (2020). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Enamel carbonate (δ 13 C apatite ) values plotted against dentinal collagen (δ 13 C collagen ) values. MS1‐4 (red circles) are individuals from the Dee St assemblage and MS6 is the modern individual (yellow circle), dietary lines generated using data from King et al (2020). …”
Section: Resultsmentioning
confidence: 99%
“…Comparison of Dee St 87 Sr/ 86 Sr and δ 18 O values plotted in reference to isotope values from the early colonial cemeteries in the Otago region from King et al (2020) and King, Buckley et al (2021). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This percentage is comparable to a cohort of adults (86%) with enamel hypoplastic defects who were migrants to Milton, New Zealand, during the 19 th century [ 100 ]. Isotopic analysis of this New Zealand cohort indicated that none of them were born locally [ 107 ], thus the health insult that caused the enamel hypoplastic defects would have occurred in their home country [ 100 ]. This is also highly likely for the adults in the St Mary’s sample.…”
Section: Discussionmentioning
confidence: 99%